Interventions to reduce tuberculosis mortality and transmission in low- and middle-income countries - Borgdorff Martien W.; Floyd Katherine; Broekmans Jaap F. (The World Health Organization, 2002)
Tuberculosis is among the top ten causes of global mortality and affects low-income countries in particular. This paper examines, through a literature review, the impact of tuberculosis control measures on tuberculosis mortality and transmission, and constraints to scaling-up. It also provides estimates of the effectiveness of various interventions using a model proposed by Styblo. It concludes that treatment of smear-positive tuberculosis using the WHO directly observed treatment, short-course (DOTS) strategy has by far the highest impact. While BCG immunization reduces childhood tuberculosis mortality, its impact on tuberculosis transmission is probably minimal. Under specific conditions, an additional impact on mortality and transmission can be expected through treatment of smear-negative cases, intensification of case-finding for smear-positive tuberculosis, and preventive therapy among individuals with dual tuberculosis-HIV infection. Of these interventions, DOTS is the most cost-effective at around US$ 5-40 per disability-adjusted life year (DALY) gained. The cost for BCG immunization is likely to be under US$ 50 per DALY gained. Treatment of smear-negative patients has a cost per DALY gained of up to US$ 100 in low-income countries, and up to US$ 400 in middle-income settings. Other interventions, such as preventive therapy for HIV-positive individuals, appear to be less cost-effective. The major constraint to scaling up DOTS is lack of political commitment, resulting in shortages of funding and human resources for tuberculosis control. However, in recent years there have been encouraging signs of increasing political commitment. Other constraints are related to involvement of the private sector, health sector reform, management capacity of tuberculosis programmes, treatment delivery, and drug supply. Global tuberculosis control could benefit strongly from technical innovation, including the development of a vaccine giving good protection against smear-positive pulmonary tuberculosis in adults; simpler and shorter drug regimens for treatment of tuberculosis disease and infection; and improved diagnostics for tuberculosis infection and disease.